2017
DOI: 10.1093/brain/aww284
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation interventions for addictive disorders: challenges, promise, and roadmap for future research

Abstract: Addictive disorders are a major public health concern, associated with high relapse rates, significant disability and substantial mortality. Unfortunately, current interventions are only modestly effective. Preclinical studies as well as human neuroimaging studies have provided strong evidence that the observable behaviours that characterize the addiction phenotype, such as compulsive drug consumption, impaired self-control, and behavioural inflexibility, reflect underlying dysregulation and malfunction in spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 179 publications
(188 reference statements)
1
60
0
Order By: Relevance
“…In a later phase of TBI, it was possible to observe motor recovery as well as spatial memory improvement following repeated anodal tDCS [48]. A growing number of studies has been reporting promising effects of neurostimulation in models of addictive disorders, by reducing craving and maladaptive pervasive learning [49]. In fact, repeated anodal stimulation in mouse frontal cortex decreased nicotine-induced conditioned place preference and further improved working memory [50].…”
Section: Neural Plasticitymentioning
confidence: 99%
“…In a later phase of TBI, it was possible to observe motor recovery as well as spatial memory improvement following repeated anodal tDCS [48]. A growing number of studies has been reporting promising effects of neurostimulation in models of addictive disorders, by reducing craving and maladaptive pervasive learning [49]. In fact, repeated anodal stimulation in mouse frontal cortex decreased nicotine-induced conditioned place preference and further improved working memory [50].…”
Section: Neural Plasticitymentioning
confidence: 99%
“…Active tDCS versus sham has been shown to enhance the effects of cognitive training in a number of domains, including inhibitory control, memory, attention, and other forms of cognition (Coffman et al., ). There have been over 250 clinical trials using tDCS for a variety of disorders and diseases, and there are also preliminary data suggesting tDCS has an effect on addictive disorders (Boggio et al., ; Coles et al., ; Feil and Zangen, ; Lapenta et al., ; Spagnolo and Goldman, ; Trojak et al., ). Specifically, tDCS has been shown to impact inhibitory control (Levasseur‐Moreau and Fecteau, ; Stramaccia et al., ), and cue reactivity and craving (Jansen et al., ; Nardone et al., ).…”
Section: Behavioral and Neurobiological Dysfunction In Audmentioning
confidence: 99%
“…Interestingly, desire to gamble was measured before and after subjects performed a 15‐min slot machine game session, which preceded the stimulation. Several rTMS studies in SUDs have shown that using tasks and cue‐reactivity procedures to engage targeted circuits may improve stimulation outcomes (Hanlon et al ., ; Spagnolo & Goldman, ). Additionally, in this study, TMS effects on delay discounting and cognitive processes were also evaluated using the delay discounting and the Stroop interference task, with negative results (Zack et al ., ).…”
Section: A Potential Therapeutic Approach Targeting Craving States Inmentioning
confidence: 99%